Attitudes, Sentiments, and Concerns About Inclusive Education of Teachers and Teaching Students in Spain - Navarro-Mateu, Diego; Franco-Ochoa, Jacqueline; Valero-Moreno, Selene; Prado-Gascó, Vicente (Frontiers in Psychology, 2020)
The Sentiments, Attitudes, and Concerns About Inclusive Education Revised scale was developed to close the existing gap in measuring perceptions of inclusive education in the educative context. It has been widely used in other cultures but not in Spain. Our objective has been to analyze the psychometric properties in the Spanish sample by studying their relationship with empathy and social dominance variables, finally taking into account sociodemographic variables to observe if there are differences. The scale was applied to a total of 647 subjects: 323 university-students (18–45 years) and 324 in-service teachers (35–58 years). The scale showed psychometric properties suitable for the general group, the students, and the teachers. Likewise, the female students showed a more positive attitude toward inclusion, and these attitudes were associated with empathy and social dominance. This version of the Sentiments, Attitudes, and Concerns about Inclusive Education Revised is a useful tool for measuring the inclusive attitudes of undergraduate education students and in-service teachers.